Human aggression (Part 12) - Jumat, Rahiman (2012)
We can do it by apologizing and letting they know that you understand that your actions led them to this stress. If someone is about to push you, you can either back away or confront their advances. Confronting their advances only deepens the well of discord and creates a fight, but by intelligently backing off, their aggression is immediately defused.